Dynamic event-triggered fuzzy non-fragile control of DC microgrids - Li, Fuqiang; Li, Kang; Peng, Chen; Gao, Lisai (ISA transactions, 2023)
This paper studies the event-triggered fuzzy non-fragile control of uncertain DC microgrids subject to false data injection (FDI) attacks, controller saturation, network delays and premise mismatching. Firstly, a dynamic event-triggered mechanism (ETM) is proposed, which can save more communication bandwidth than the static ETMs, and remove the complex Zeno-free computation required by the continuous-time ETMs. Secondly, a fuzzy time-delay closed-loop system model is established, which provides a unified framework to study the effects of the dynamic ETM, FDI attacks, uncertainties, saturation, delays and premise mismatching. Thirdly, mean-square exponential stability criteria are established, and co-design method for the saturated fuzzy non-fragile (SFNF) controller and the dynamic ETM is presented. Simulation results confirm that the SFNF controller can stabilize the unstable DC microgrid, while the dynamic ETM significantly reduces the triggering rate by 84.98%. Comparisons show that the proposed controller performs better than the non-fragile controller, fuzzy controller and robust linear controller, and the dynamic ETM achieves a lower triggering rate than the static ETMs. •A novel dynamic event-triggered mechanism is proposed for DC microgrids with CPLs.•A unified fuzzy time-delay closed-loop system model is established.•A saturated fuzzy non-fragile injection current controller is designed.